Unintended Consequences: New Problems, New Solutions - Koppel, R.; Chen, Y.; Section Editors for the IMIA Yearbook Special Section on Unintended Consequences (Yearbook of Medical Informatics, 2016)
Objective: To select the best of the 2015 published papers on unintended consequences of healthcare information technology (HIT).Method: Literature searches in several areas of scholarship, including IT, human factors, evaluation studies, medical errors, medical informatics, and implementation science. Also, because the specific terms “unintended consequences” were not often included in abstracts and titles, a more nuanced search algorithm was developed.Results: We identified 754 papers that had some empirical research on unintended consequences of HIT. An initial screen of titles and abstracts reduced this to 171 papers of potential interest. We then further filtered out papers that did not meet the following criteria: 1) the paper had to report an original empirical investigation, and 2) the impact reported had to be not negligible, i.e., in quantitative studies, the results related to unintended consequences were statistically significant; and in qualitative studies the relevant themes emerged were prominent. This resulted in 33 papers of which 15 were selected as best paper candidates. Each of these 15 papers was then separately evaluated by four reviewers. The final selection of four papers was made jointly by the external reviewers and the two section editors. Conclusions: There is a growing awareness of the importance of HIT’s unintended consequences—be they generated by the HIT vendors, the implementation process, the consultants, the users, or most probably, some combination of the above. There has also been greater creativity in use of data sources, including secondary data (e.g., medical malpractice cases and surveys) and a wider acceptance of mixed methods to identify unintended consequences. Unfortunately, the complexity of causes mitigates the value of recommendations to avoid unwanted outcomes. Suggestions are often contentious rather than obvious, setting-specific, and not universally applicable. “Lessons learned” often take on generalized—and perhaps platitudinous—forms, such as: “plan extra time,” “involve all of the stakeholders,” “recognize the different needs of different units or disciplines.” The greater awareness of these problems, and the increased desire to identify and eliminate them is clearly reflected in the area’s growing literature. We are hopeful the topic will receive additional attention and the discipline will improve its ability to identify and address these unexpected and usually adverse outcomes.
Keywords: Medical informatics; adverse events; International Medical Informatics Association; yearbook; unintended consequences